FXR Activation Accelerates Early Phase of Osteoblast Differentiation Through COX-2-PGE2-EP4 Axis in BMP-2-Induced Mouse Mesenchymal Stem Cells - Ko Fujimori; Yusuke Iguchi; Yukiko Yamashita; Keigo Gohda; Naoki Teno (Molecules)
Farnesoid X receptor (FXR), a nuclear receptor, is expressed in calvaria and bone marrow stromal cells and plays a role in bone homeostasis. However, the mechanism of FXR-activated osteoblast differentiation remains unclear. In this study, we investigated the regulatory mechanism underlying FXR-activated osteoblast differentiation using bone morphogenetic protein-2 (BMP-2)-induced mouse ST-2 mesenchymal stem cells. We also synthesized a novel FXR agonist, FLG390, and compared its biological effects in osteoblast differentiation with a known FXR agonist, chenodeoxycholic acid (CDCA). As an FXR agonist, FLG390 accelerated osteoblast differentiation to a comparable extent with CDCA, enhancing alkaline phosphatase (ALP) activity and the expression of osteoblast differentiated-related genes such as ALP, collagen type 1 α1 chain (COL1A1), and runt-related transcription factor 2 (RUNX2). FXR activation elevated the expression of cyclooxygenase (COX)-2 and the production of prostaglandin (PG) E2 in the early phase of osteoblast differentiation. A selective COX-2 inhibitor and an antagonist of EP4 receptors, one of PGE2 receptors, partially suppressed FXR-activated osteoblast differentiation. Moreover, treatment with either inhibitor during the first 6 h after initiating osteoblast differentiation repressed FXR-activated osteoblast differentiation to the same extent as did the treatment for 6 d. Therefore, a novel FXR agonist, FLG390, exhibited potency comparable to CDCA. FXR activation promoted the early phase of osteoblast differentiation via the COX-2-PGE2-EP4 axis, representing a potential target for control of bone metabolism.